Ciberespaço, técnica e hermenêutica: diálogos da ciência da informação - Oliveira, Walter Clayton de [UNESP] (2013)
The theme of this study is the dialogue of information science with cyberspace, technology and hermeneutics. The discussion is mainly theoretical-philosophical. As a zone contiguous virtual to the real world, cyberspace should be thought of as providing a layer technique-electronics where promote cognitive operations, complicating the universe of human experience. The objectives of the study: to present a reflection on the constitution and design of cyberspace characteristic postmodern and its interface with technique, reflect on the creation of a science postmetaphysical referenced by hermeneutics and its interrelation theoretical and philosophical with information science. The methodology intends, through reading and conversation with authors who are linked to the most recent discussion of the epistemology of science, among others, the joints and exhibitions of the arguments of the thesis. The originality of the text builds on display, in argument and theoretical-philosophical intended between modern science, technology and science post-metaphysical hermeneutics and their interrelationships, for the creation of a sociotechnical knowledge. The result of this thesis is primarily an argument about the scope of a theoretical and philosophical information science reenchanted by hermeneutic knowledge